2018
DOI: 10.1159/000487960
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Features of Delayed Clinical Progression in Cerebral Venous Thrombosis: A Proposed Prediction Score for Early Intervention

Abstract: Background: Anticoagulation is the mainstay treatment for cerebral venous thrombosis (CVT). A subset of patients might deteriorate despite anticoagulation, and in such cases, endovascular therapy is recommended. Methods: A retrospective review was performed on subjects with CVT from January 2005 to October 2016. The primary outcome was clinical deterioration. Bivariate analysis, multiple logistic regression modeling, and linear discriminant analysis were used to determine a predictive model for deterioration; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
(27 reference statements)
2
23
0
Order By: Relevance
“…CVT was earlier considered as a disease of females, as demonstrated by many previous studies done abroad and in India and especially occurred during pregnancy and puerperium but studies done nowadays showed male preponderance with alcoholism and hyperhomocysteinemia as predominant risk factors and is usually seen in young individuals. [11][12][13][14][15][16][17][18][19][20] Study also proved same findings with preponderance of disease in young males. In contrast to some other studies done in India which showed a predominant sub acute mode of onset, our study most of the patients had acute onset of disease.…”
Section: Discussionsupporting
confidence: 58%
“…CVT was earlier considered as a disease of females, as demonstrated by many previous studies done abroad and in India and especially occurred during pregnancy and puerperium but studies done nowadays showed male preponderance with alcoholism and hyperhomocysteinemia as predominant risk factors and is usually seen in young individuals. [11][12][13][14][15][16][17][18][19][20] Study also proved same findings with preponderance of disease in young males. In contrast to some other studies done in India which showed a predominant sub acute mode of onset, our study most of the patients had acute onset of disease.…”
Section: Discussionsupporting
confidence: 58%
“…However, (2020) 10:4937 | https://doi.org/10.1038/s41598-020-61884-5 www.nature.com/scientificreports www.nature.com/scientificreports/ questions about the safety and validity of the endovascular treatment plus heparin for CVST over the heparin treatment alone in the acute phase have not been answered 9,12,[18][19][20] . In the literature, a subgroup of CVST patients who harbored risk factors known for poor prognosis and mortality (e.g., decreased level of consciousness, coma, and seizure activity) were oftentimes unresponsive to systemic heparin treatment in the acute phase 4,5,[7][8][9] . In this study, all of the patients in D group had initial complete stenosis of the sinuses (type B or type D), with higher mRS (p = 0.006), lower GCS (p = 0.007), and more seizures (p = 0.031) at initial presentation, which reflected the disease severity and high risks of poor outcome and mortality in the acute phase 4,5,[7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a subgroup of CVST patients who harbored risk factors known for poor prognosis and mortality (e.g., decreased level of consciousness, coma, and seizure activity) were oftentimes unresponsive to systemic heparin treatment in the acute phase 4,5,[7][8][9] . In this study, all of the patients in D group had initial complete stenosis of the sinuses (type B or type D), with higher mRS (p = 0.006), lower GCS (p = 0.007), and more seizures (p = 0.031) at initial presentation, which reflected the disease severity and high risks of poor outcome and mortality in the acute phase 4,5,[7][8][9] . In I/S group, patients were responsive to heparin with milder initial presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) The American Heart Association (AHA) guidelines recommend anticoagulant therapy and state that endovascular treatment should be considered for patients with symptom progression. 3) However, symptoms deteriorate in 24-25.8% of patients with cerebral sinus thrombosis, 4,5) and early endovascular treatment may improve the outcome in patients in whom symptoms are expected to deteriorate. 5) We report a patient with cerebral sinus thrombosis with venous congestion for whom mechanical thrombectomy was performed on the day of arrival, leading to a favorable outcome.…”
Section: Introductionmentioning
confidence: 99%